Causes Of Premature Death And Associated Risk Factors In Golestan Province, Iran - Oranuba, Ebele (My University, 2018)
Premature death is devastating and about 86% of global premature deaths occur in low and middle-income nations. This study examines causes of premature death and associated risk factors in a Golestan population located in the northeastern region of Iran - an upper-middle income country. Data was analyzed for participants (N=50,045) recruited into the Golestan Cohort Study (GCS) from study period 2004 to August 2017; Causes of premature mortality, burden of these causes, their associated modifiable risk factors and Population Attributable Fraction (PAF) of the significant risk factors were determined. The participants were followed for a total of 444168 person-years (median years of follow-up =10 years). Of 6347 deaths in the cohort, 4018 (63.3%) of occurred prematurely. Leading causes of premature mortality include Ischemic heart disease (33.9%), stroke (14.0%), road injuries (4.7%), stomach cancer (4.6%), and esophageal cancer (4.6%). Significant predisposing/protective factors include wealth score (HR for highest vs lowest quintile: 0.57, PAF for lowest four quintiles vs top quintile: 28%), physical activity (highest vs lowest tertile: 0.67, lowest two tertiles vs top tertile: 26%), opium use (1.69, 19%), tobacco use (1.38, 17%), hypertension (1.50, 17%), education (middle-school or higher vs illiterate: 0.84, illiterate or primary vs middle-school or higher: 11%), vegetable-fruit consumption (highest vs lowest tertile: 0.87, lowest two tertiles vs top tertile: 7%), and diabetes (2.39, 6%). Collectively, these factors accounted for 73% of PAF (69% in women; 73% in men). In conclusion, this study shows that the leading causes of death in this population are non-communicable diseases including ischemic heart disease and stroke. In order to improve life expectancy, this population will greatly benefit from policies that target improving socioeconomic risk factors and interventions that aim at reducing death from road injuries and chronic diseases including circulatory diseases and neoplasms.
Keywords: Iran; Premature death; Public health; Premature death; Middle East